Astrocyte and glutamate involvement in the pathogenesis of epilepsy in Alzheimer's disease. (10th May 2021) - Dejakaisaya, Hattapark; Kwan, Patrick; Jones, Nigel C.
Abstract: Alzheimer's disease (AD) can increase the risk of epilepsy by up to 10‐fold compared to healthy age‐matched controls. However, the pathological mechanisms that underlie this increased risk are poorly understood. Because disruption in brain glutamate homeostasis has been implicated in both AD and epilepsy, this might play a mechanistic role in the pathogenesis of epilepsy in AD. Prior to the formation of amyloid beta (Aβ) plaques, the brain can undergo pathological changes as a result of increased production of amyloid precursor protein (APP) and Aβ oligomers. Impairments in the glutamate uptake ability of astrocytes due to astrogliosis are hypothesized to be an early event occurring before Aβ plaque formation. Astrogliosis may increase the susceptibility to epileptogenesis of the brain via accumulation of extracellular glutamate and resulting excitotoxicity. Here we hypothesize that Aβ oligomers and proinflammatory cytokines can cause astrogliosis and accumulation of extracellular glutamate, which then contribute to the pathogenesis of epilepsy in AD. In this review article, we consider the evidence supporting a potential role of dysfunction of the glutamate‐glutamine cycle and the astrocyte in the pathogenesis of epilepsy in AD.